A Study on the Synthesis and Characterization of hydroxypropyl Cyclodextrin and Cyclodextrininclusion Complexes (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The aim of this study is to the Cyclodextrins have a wide range of applications in different areas of drug delivery and pharamaceutical industry, due to their complexation ability and other versatile characteristics. Improving the solubility, stability, protection and bioavailability of medicinal molecules is the most common pharmaceutical application. The medicines are currently solubilised by using β-CDs and rendering bioavailable. These works focus on the improved solubility and bioavailability of anti-malaria drugs such as quinine sulphate, sulphatehydroxychloroquine, hydrochlorinemefloquine, phosphate chloroquine and phosphate premaquine, having poor water solubility and therefore low bioavailability. This study is focused on the findings. The scope of this study is therefore to boost drug solvency through the development of α-cyclodextrin and Hydroxypropylα-cyclodextrin inclusion complexes. In addition, in pharamaceutical applications cyclodextrins are strong nanocarriers. Cyclodextrins are macrocyclic oligosaccharides made up respectively of 6,7 or 8 units of glucopyranose known as α, β and CDs. These units are connected by glucosidic connecting elements -(1,4) and are all glucose molecules in C1. CDs are hydrophilic compounds with a hydrophobic cavity that enables them to create water-based inclusion complexes. Entry into the CD cavity changes the physicochemical characteristics of a compound used. CDs are one of the most significant supramolecular family members used in the food, pharmaceutical and home-grown industries. CDs are naturally occurring compounds which can be developed on a large scale through bacterial fermentation. The other big benefit of CDs relative to other carbohydrates is that they are extremely water soluble and human not toxic. This section seeks to provide a brief overview of CD physicochemical characteristics, synthesis, and complex formation of the inclusion and some of its applications. The work in this thesis concerns CDs and HP-CDs exclusively